The influence of anti-HBc status on the sustained virological response rate in HCV-infected patients treated with pegylated interferon alfa 2 and ribavirin - Szymanek-Pasternak, Anna; Simon, Krzysztof A.; Serafińska, Sylwia; Janocha-Litwin, Justyna; Pazgan-Simon, Monika; Madej, Grzegorz (Clinical and Experimental Hepatology, 2016)
Aim of the study : To determine the influence of HBsAg and HBeAg negative but anti-HBc positive status on the sustained virological response (SVR) rate in HCV-infected patients treated with pegylated interferon alfa 2 (Peg-IFNα-2) and ribavirin (RBV). Material and methods: The study was based on the retrospective analysis of medical records of HCV-infected patients who started Peg-IFNα and RBV treatment between 1 January 2011 and 31 December 2013 at the 1st and 2nd Department of Infectious Diseases of the Regional Hospital in Wrocław, Poland. Results : Among 240 patients included in the analysis 99 were anti-HBc positive and 141 anti-HBc negative. In the genotype 1, anti-HBc positive group the SVR rate was 47% and in the anti-HBc negative group it was 42.7% (p = 0.591). In the genotype 3, anti-HBc positive group the SVR rate was 60% and in anti-HBc negative patients it was 63.2% (p = 0.79). Differences in SVR rates between anti-HBc positive and negative groups were not statistically significant. None of the anti-HBc positive patients developed reactivation of HBV infection during or in the 24 weeks following the end of treatment. Conclusions : Anti-HBc determination does not seem to be useful in predicting treatment outcome of conventional Peg-IFNα/RBV therapy in patients infected with HCV genotypes 1 and 3.